2022
DOI: 10.3389/fimmu.2022.978591
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of BK-SE36 in a blinded, randomized, controlled, age de-escalating phase Ib clinical trial in Burkinabe children

Abstract: BackgroundA blood-stage vaccine targeting the erythrocytic-stages of the malaria parasite Plasmodium falciparum could play a role to protect against clinical disease. Antibodies against the P. falciparum serine repeat antigen 5 (SE47 and SE36 domains) correlate well with the absence of clinical symptoms in sero-epidemiological studies. A previous phase Ib trial of the recombinant SE36 antigen formulated with aluminum hydroxyl gel (BK-SE36) was promising. This is the first time the vaccine candidate was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The epitope mapping data suggest that (i) intrinsically unstructured regions allow some flexibility for the epitopes to interact with other molecules/proteins; (ii) the regions adjacent to the repeats are not strictly disordered as they showed a tendency to form a secondary structure; (iii) the protective epitopes of BK-SE36 are located in the N-terminal region where the repeat number of octamer units varied among alleles; and (iv) serum from mice and squirrel monkeys vaccinated with BK-SE36 also showed a broad range of reactivity against peptides covering the SR region (Yagi et al, 2014). Indeed, serum samples from clinical trial participants that received BK-SE36 preferentially recognized epitopes corresponding to the SR and flanking regions (including 13mer insertion/deletion, polyserine residue and 17-mer dimorphic region) (Ezoe et al, 2020;Bougouma et al, 2022). Thus, these indicate that the antibodies induced by BK-SE36 vaccination bound, with reproducibility, to epitopes located in the disordered regions of the protein.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The epitope mapping data suggest that (i) intrinsically unstructured regions allow some flexibility for the epitopes to interact with other molecules/proteins; (ii) the regions adjacent to the repeats are not strictly disordered as they showed a tendency to form a secondary structure; (iii) the protective epitopes of BK-SE36 are located in the N-terminal region where the repeat number of octamer units varied among alleles; and (iv) serum from mice and squirrel monkeys vaccinated with BK-SE36 also showed a broad range of reactivity against peptides covering the SR region (Yagi et al, 2014). Indeed, serum samples from clinical trial participants that received BK-SE36 preferentially recognized epitopes corresponding to the SR and flanking regions (including 13mer insertion/deletion, polyserine residue and 17-mer dimorphic region) (Ezoe et al, 2020;Bougouma et al, 2022). Thus, these indicate that the antibodies induced by BK-SE36 vaccination bound, with reproducibility, to epitopes located in the disordered regions of the protein.…”
Section: Discussionmentioning
confidence: 91%
“…If this interpretation is true, young children or individuals with limited malaria infection history would respond better to BK-SE36 vaccination similar to malaria naïve Japanese adults. Indeed, the seroconversion rate was higher in the 24-60-month-old and 12-24-month-old Burkinabe children (79-83% after two-and 89-97% after three-vaccinations) (Bougouma et al, 2022). This immune tolerance could also explain why SERA5 is less likely to be under substantial immune selection pressure compared to other blood-stage malaria vaccine antigens such as AMA1 and CSP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Phase I safety and immunogenicity trials of BK-SE36 were conducted in healthy, malaria-naïve Japanese adults ( 10 ), in malaria-exposed Ugandan volunteers aged 6- to 32-year-old ( 21 ), and in healthy 12- to 60-month-old Burkinabe children ( 22 ). These trials have demonstrated the safety and immunogenicity of BK-SE36.…”
Section: Introductionmentioning
confidence: 99%